Associated macrozoobenthos with the invasive Asian clam Corbicula fluminea - Ilarri, Martina I. (2012)
The Asian clam Corbicula fluminea is one of the most invasive species in brackish and freshwater ecosystems. In the Minho estuary (NW of the Iberian Peninsula) this invasive species can reach densities up to 4000 ind m−2, occurring over large areas. C. fluminea can significantly alter the physical structure of the benthic environment, and the structure and functioning of this estuarine community. In this context, this work aimed to evaluate the correlation of different densities of C. fluminea on the macrozoobenthos across five sites in the Minho estuary during three distinct periods of 2009 (winter, spring and summer). The comparative analysis indicate that macrozoobenthic density, biomass and diversity positively respond to increasing density of C. fluminea, with abiotic conditions also playing an important role in the observed patterns, both in brackish and freshwater settings. Crustacea, Insecta and Gastropoda are the main faunal groups responding positively to C. fluminea increasing density. The mechanisms responsible for these positive trends still needs to be established although engineering activities and the increase in waste products may play essential roles. Nevertheless, despite such positive effects, earlier studies have showed that the density, biomass and spatial distribution of some species, especially native bivalves dramatically decreased after C. fluminea introduction.